The interaction problem of two Zener–Stroh cracks with a nearby inhomogeneity - Fan, M. (2021)
In this paper, the interaction among two Zener–Stroh cracks (with plastic zone correction) and a nearby circular inclusion are investigated. To evaluate the plastic zone sizes at crack tips in the current physical problem is a great challenge. As the first attempt to explore the multiple defects’ interaction effect on the yielding behavior of a crack, we focused on the analysis of one target crack, while the other crack and the circular inhomogeneity are treated as influence factors. With the help of coordinate transformation and superposition procedure, the formulated singular integral equations can be solved numerically. The influence of material properties, crack–crack positions and other parameters, such as crack length and Burgers vector of the Zener–Stroh crack, on the target crack tip stress intensity factor, plastic zone size and crack tip opening displacement are examined. It is found that the effects of the aforesaid parameters on the cracks are all inter-related and dependent on each other. This observation reveals the complexity of fracture analysis and the necessity to have a deep research on interacting defects in composite materials.